The removal of neonicotinoid insecticide imidacloprid in an annular photoreactor - Babić, Kristina, kemijska inženjerka; Tomašić, Vesna, kemičarka; Grčić, Ivana; Duplančić, Marina; Gomzi, Zoran (2020)
Heterogeneous photocatalysis has recently attracted an increasing interest of scientists and experts who deal with the waste water and air treatment. An important area of application is removal of persistent organic pollutants, which can not be easily destroyed by conventional methods. Among these pollutants are neonicotinoid insecticides, which are widely used all over the world and currently are included in the watch list of substances of the European Commission within the Water Framework Directive. Therefore, there is a need to study their influence on the environment and to develop appropriate technologies for their removal. In this work, the photolytic and photocatalytic degradation of neonicotinoid insecticide imidacloprid in an annular photoreactor with recirculation under different working conditions (irradiation source, pH, type and concentration of the catalyst) was studied. The photolytic degradation was examined using lamps that emit UVA, UVC and simulated sun light. The photocatalytic experiments in the suspension involved the use of commercial titanium dioxide (TiO2 P25, Degussa/Evonik), commercial TiO2 P25 pre-treated with UVC irradiation prior to use in the catalytic system and nitrogen-doped TiO2 (CCR 200 N produced by Cinkarna Celje). The catalysts were characterized using XRD, UV/Vis-DRS and BET analysis. The most efficient photocatalyst was then immobilized on the glass woving fibre, using peroxotitanic acid (produced by Cinkarna Celje) as a binder. The degree of degradation of imidacloprid was determined using high performance liquid chromatography (HPLC). According to the obtained results, UVC-treated TiO2 showed the best efficiency among the examined catalysts in the slurry reactor while using lamp that simulates the sun irradiation. The imidacloprid degradation rate increases with the increase in the catalyst concentration. The immobilized UVC-treated catalyst gave satisfying results in terms of stability, activity and reuse.
Bibliografija: 12 jed.
Summary.
Keywords: Heterogena fotokataliza -- Neonikotinoidni insekticidi -- Imidakloprid -- Prstenasti reaktor